NILAI EKONOMI OBJEK WISATA BERBASIS JASA EDUKASI PERTANIAN DI SENTULFRESH INDONESIA KECAMATAN SUKARAJA, KABUPATEN BOGOR - Mahardika, Desi Aditia; Arifin, Bustanul; Nugraha, Adia (Lampung University, 2019)
This study aims to examine the factors that influence the frequency of tourist visits, find out the willingness to pay admission tickets, and analyze the economic value of Tourism Destination Sentulfresh Education Farm in Bogor District. The research location was chosen deliberately in Indonesian Sentulfresh, Sukaraja Subdistrict of Bogor District. The sample in this study was 68 respondents for original visitors and potential visitors from Sentulfresh Education Farm who were selected by accidental sampling methods with criteria of age 17 years and above. Research data collection were conducted in March-May 2018. The analytical method used in this study were qualitative descriptive analysis and quantitative descriptive analysis. The results showed that: Frequency of tourist visits was influenced by travel costs, education level, income, and distance. Willingness to pay entrance fees by visitors to the tourism destination of Sentulfresh Education Farm in Bogor District was Rp75.367,65/individual for happy kids tour packages, Rp95.220,59/individual for super kids tour packages, and Rp71.323,53/individual for parent travel packages. The total economic value of the Tourist Destination for Sentulfresh Education Farm in Bogor District was Rp11.101.412.264,62 with the value of the consumer surplus/individual/visit of Rp504.082,65. Key words: economic value, sentulfresh, tourism, travel cost